A Snapshot on the Quality of Seven Home Visit Parenting Programs in Latin America and the Caribbean - Jane Leer; Florencia López Bóo; Ana Perez Expósito; Christine Powell (Institute for the Study of Labor (IZA), 2016)
Although there is ample support for the causal link between home visit parenting programs and child development outcomes, few studies have explored what it is that drives this relationship – to what extent home visit programs are implemented as designed in terms of the content and strategies used by home visitors. To our knowledge, comparable data on the quality and fidelity of implementation in home visit programs in Latin America and the Caribbean (LAC) does not exist. In light of this gap, this note presents a snapshot of home visit quality in seven countries in which home visits reach a considerable number of children. Using an observational checklist tool, we find strong rapport between visitors and families, and consistent involvement of caregivers and children in practicing activities during the visit. However, visitors rarely explain the importance of these activities in relation to child development, often times do not bring the necessary materials, and do little to encourage meaningful dialogue and feedback from caregivers nor demonstrate the desired activity or behavior. Only one third of the observed visitors emphasized language development throughout the visit. It is important to emphasize that these results are not generalizable due to the small and non-random nature of the sample of home visits observed. Nonetheless, this study serves as a pilot of the instrument and type of domains that can and should be measured in a home visit program in order to ensure implementation quality.
Keywords: J13; H53; H75; I38; 330; early childhood development; quality; home visiting programs; process quality; Brazil; Nicaragua; Peru; Panama; Jamaica; Ecuador; Bolivia